2017
DOI: 10.1177/0040517517732087
|View full text |Cite
|
Sign up to set email alerts
|

Dithering method for reproducing smoothly changing tones and fine details of natural images on woven fabric

Abstract: This paper introduces novel methods to improve the aesthetic appearance of rendered grayscale digital images on woven fabric by smoothly changing tones and improving the reproducibility of fine details. The methods are based on stepping dithering, a recently developed dithering method for automatically generating jacquard weave patterns for arbitrary given images. The existing stepping dithering method suffers from two problems. The first problem is the visually unappealing repetition of patterns for input ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…9(a) shows the result of applying one stepping dither mask to an entire image. The threshold of the dither mask is optimized and partially shuffled in the dither mask in the manner proposed in [19]. Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9(a) shows the result of applying one stepping dither mask to an entire image. The threshold of the dither mask is optimized and partially shuffled in the dither mask in the manner proposed in [19]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Toyoura et al proposed a stepping dither mask that allows freer design of fabric patterns based on ordered dithering [21]. The same group also discussed the optimum setting of stepping dither masks [19]. The patterns generated with their method satisfy MCC and earn a large CFR and, therefore, can be directly used for producing fabric that is desirable both aesthetically and functionally.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…While exploring this issue, we proposed that the technique used to increase the exposure of warp and weft yarns at specific positions could be converted in such a manner as to spatially vary the electrical characteristics of e-textiles. Our idea was inspired in part by the proposed method in Igarashi et al [18] to control the intersection of yarns to faithfully reproduce tones of an arbitrary image. Their method of controlling the warps and wefts of fabric is applicable for controlling electrical properties of e-textiles.…”
Section: Design Of Nonconductive Textilesmentioning
confidence: 99%
“…12, each warp and each weft intersect more than once in an 8 × 8 square yarn of fabric, keeping form as a fabric. Igarashi et al [18] showed that exposure of weft and warp yarns that are too long results in weakness against external forces such as scratching. Exposure of the yarns can be limited by ensuring that the warp and weft yarns intersect at least once for each row and each column in each n × n unit region.…”
Section: Prototype Of Sensor For Pressure Detection and Localizationmentioning
confidence: 99%